2008
DOI: 10.1038/sj.jp.7211925
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ibuprofen L-lysinate on bilirubin binding to albumin as measured by saturation index and horseradish peroxidase assays

Abstract: Objective: To demonstrate, in vitro, the influence of increasing ibuprofen (IBU) concentration on bilirubin-albumin (B-A) binding. Study Design:The influence of IBU on B-A binding was measured by saturation index and horseradish peroxidase assays. B-A solutions were prepared at B:A ratios of 0.5, 1.0, 1.5 and 2.0 and bilirubin concentrations of 5 and 10 mg per 100 ml. Drug concentrations used were 142.5, 200 and 285 mg l À1 for IBU and 100 and 200 mg l À1 for acetyl salicylic acid (ASA). Similar tests were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 24 publications
(22 reference statements)
0
12
0
Order By: Relevance
“…Ibuprofen, one of the drugs used for treating patent ductus arteriosus in preterm infants, is a potent bilirubin displacer and has been shown to increase UB concentrations in vitro [21,22]. However, recent in-vivo studies have shown that ibuprofen does not displace bilirubin and increase UB concentrations in preterms with mild to moderate hyperbilirubinemia [23,24].…”
Section: Ibuprofenmentioning
confidence: 97%
“…Ibuprofen, one of the drugs used for treating patent ductus arteriosus in preterm infants, is a potent bilirubin displacer and has been shown to increase UB concentrations in vitro [21,22]. However, recent in-vivo studies have shown that ibuprofen does not displace bilirubin and increase UB concentrations in preterms with mild to moderate hyperbilirubinemia [23,24].…”
Section: Ibuprofenmentioning
confidence: 97%
“…41,42 In addition, at higher serum concentration ibuprofen can displace bilirubin from its binding to albumin. 38 Indeed, a recent study showed that ibuprofen augments bilirubin toxicity in rat cortical neuronal culture. 43 The clinical significance of this potential neurotoxicity remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37] Although ibuprofen appears to have a better profile with regard to renal side effects and organ blood flows, the drug's effect on bilirubin metabolism and displacement of albumin binding, and the possible but recently debated association with pulmonary hypertension, have raised concerns. [38][39][40] Ibuprofen is thought to impair biliary excretion of bilirubin and therefore it raises serum bilirubin level. 41,42 In addition, at higher serum concentration ibuprofen can displace bilirubin from its binding to albumin.…”
Section: Introductionmentioning
confidence: 99%
“…[7375] Ahlfors, et al . [74] demonstrated, using the peroxidase method, that a significant increase in UB concentration was only observed at ibuprofen concentrations >50 μg/mL in two pooled newborn sera with BAMRs of 0.3 and 0.36.…”
Section: Introductionmentioning
confidence: 99%